Research on innovative design of medical bottle opening device based on fuzzy set qualitative comparative analysis (fsQCA) - Wang Yuqing; Sun Hu (Critical Public Health)
Based on fuzzy set qualitative comparative analysis (fsQCA) research methodology, an innovative study was conducted on medical-bottle-opening devices to ensure convenience of use and reduce occupational exposure for healthcare workers. The user behavior was analyzed, and the design objectives of the product were to reduce the improper opening of the bottle mouth and prevent broken bottles, liquid splashing, and injuries to the hands of the caregivers. The fsQCA method was used to analyze the causal relationships between the use variables from a geometric point of view. The design conditions were analyzed to avoid the conflicts and contradictions in the design process and to determine how to effectively and conveniently open different types of liquid containers in medical applications. Finally, a portable medical-bottle opener was proposed to meet the needs of healthcare workers without creating an additional burden.